PENDIDIKAN ANAK PERSPEKTIF PSIKOLOGY ISLAM - Burhanuddin; Siti Rokhimah (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Childhood education is an important foundation in the formation of character, personality, and spiritual values in an individual's life. From an Islamic psychology perspective, child education is not only oriented towards cognitive and affective aspects, but also encompasses spiritual and moral dimensions derived from the teachings of the Qur'an and Hadith. This paper aims to explore the concept of child education in Islamic psychology and provide an integrative approach between the principles of modern psychology and Islamic values. The methodology used is a qualitative literature study with a descriptive-analytical approach. The results of the study indicate that Islamic psychology views children as a trust from Allah who possess a natural principle of monotheism, so education must be directed towards preserving and developing this natural principle. Effective education, according to this perspective, must include aspects of role modeling, habituation, advice, and prayer. The integration of Islamic psychology and contemporary educational practices can be a solution in shaping a generation that is intellectually intelligent and spiritually mature.